Environmental performance of a cork floating floor - Demertzi, Martha
The objective of this study is to evaluate of the environmental impacts associated with the manufacturing process of a cork floating floor, produced in Portugal, in order to identify the most significant stages and processes (hotspots) with the aim of improving the manufacturing process and the sustainability of the product. Life Cycle Assessment methodology is used by applying a cradle-to-gate approach. The results show that the stage with the highest environmental impact is the assembling stage (where all the product’s components are assembled) mainly due to the production of high density fiberboard. Additionally, the present study discusses the currently hot and controversial issue of biogenic carbon considering its storage in products and emission delay. For this part of the study a cradle-to-gate approach was adopted and three leading methodologies were compared, namely, Greenhouse Gas Protocol Product Standard, Publicly Available Specifications 2050 and the International Reference Life Cycle Data System. The results show that the choice of methodology has an important influence on the results obtained both for biogenic carbon dioxide emissions and carbon storage. This highlights the need for the establishment of a common methodology for the calculation of biogenic carbon, not only for the homogeneity of the guidelines but also for the ease of comparing results.